Ҷои №1 барои рекламаи шумо!

Барои робита: oftob.com@gmail.com

Формулаҳо барои квадратҳо

\((a + b)^2 = a^2 + 2ab + b^2\)

\((a - b)^2 = a^2 - 2ab + b^2\)

\(a^2 - b^2 = (a + b)(a - b)\)

 

Формулаҳо барои кубҳо

\((a + b)^3 = a^3 + 3a^2b + 3ab^2 + b^3\)

\((a - b)^3 = a^3 - 3a^2b + 3ab^2 - b^3\)

\(a^3 + b^3 = (a + b)(a^2 - ab + b^2)\)

\(a^3 - b^3 = (a - b)(a^2 + ab + b^2)\)
 

Формулаҳо барои дараҷаи чорум

\((a + b)^4 = a^4 + 4a^3b + 6a^2b^2 + 4ab^3 + b^4\)

\((a - b)^4 = a^4 - 4a^3b + 6a^2b^2 - 4ab^3 + b^4\)

 \(a^4 - b^4 = (a - b)(a + b)(a^2 + b^2)\); ҳосил мешавад аз \(a^2 - b^2 = (a + b)(a - b)\).